2001
DOI: 10.1094/cchem.2001.78.2.186
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sucrose on Glass Transition, Gelatinization, and Retrogradation of Wheat Starch

Abstract: Cereal Chem. 78(2): [186][187][188][189][190][191][192] Differential scanning calorimetry (DSC) was used to study the effect of sucrose on wheat starch glass transition, gelatinization, and retrogradation. As the ratio of sucrose to starch increased from 0.25:1 to 1:1, the glass transition temperature (T g , T g ′) and ice melting enthalpy (∆H ice ) of wheat starch-sucrose mixtures (with total moistures of 40-60%) were decreased to a range of -7 to -20°C and increased to a range of 29.4 to 413.4 J/g of starch,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 13 publications
3
22
0
Order By: Relevance
“…So far, related studies have mainly focused on chemical ways to use emulsifiers or other materials with high moisture retention (Kim et al, 2007, Jang et al, 2004. Unlike those studies, the present study was conducted in light of the processing methods for traditional Korean foods with a variety of properties in which the same grain is used, such as cooked glutinous rice, sticky rice cakes, and traditional cookies (Wu et al, 2009, Yoo et al, 2001.…”
Section: Resultsmentioning
confidence: 99%
“…So far, related studies have mainly focused on chemical ways to use emulsifiers or other materials with high moisture retention (Kim et al, 2007, Jang et al, 2004. Unlike those studies, the present study was conducted in light of the processing methods for traditional Korean foods with a variety of properties in which the same grain is used, such as cooked glutinous rice, sticky rice cakes, and traditional cookies (Wu et al, 2009, Yoo et al, 2001.…”
Section: Resultsmentioning
confidence: 99%
“…Carvalho and Mitchell (2000) found that the sectional expansion of wheat flour extrudates was less affected by sucrose than by corn grit extrudates, which was attributed to the starch molecular integrity of wheat being lower than corn starch under severe shear condition. Structural changes have also been attributed to competition for water (HSIEH;PENG;HUFF, 1990) and inhibition of starch gelatinization (JANG et al, 2001). The modification of the extrudate texture as a consequence of increasing the sucrose concentration has been attributed to the plasticization of starch-based products by decreasing the glass transition temperature, increasing product density, and reducing sectional expansion (FAN; MITCHELL; BLANSHARD, 1996).…”
Section: Water Absorption Index (Wai) and Water Solubility Index (Wsi)mentioning
confidence: 99%
“…Solutions of low molecular weight sugars have T g ' values below normal frozen storage temperatures (e.g. T g ' of a sucrose/water solution is around − 46°C), but for a gelatinized starch water system the T g ' is according to a number of studies around − 5°C (Ferrero, Martino, & Zaritzky, 1996;Jang, Lee, Cho, & Pyun, 2001;Levine & Slade, 1986;Lim, Wu, & Reid, 2000;Roos & Karel, 1991;Wang & Jane, 1994). The reported T g ' value for a starch/ water system is well above the storage temperature (− 24°C) used in this study and therefore the observed storage stability is not surprising.…”
Section: Effect Of Storage On Pore Size Distributionmentioning
confidence: 99%